2003
DOI: 10.4049/jimmunol.170.2.719
|View full text |Cite
|
Sign up to set email alerts
|

Decreased E12 and/or E47 Transcription Factor Activity in the Bone Marrow As Well As in the Spleen of Aged Mice

Abstract: The E2A-encoded transcription factors E12 and E47 are key regulators of B cell functions. They bind to the E-box site, found in regulatory regions of B cell-specific genes; promote cell survival of early pre-B cells; help to initiate Ig rearrangements; and are also involved in class switch in mature B cells in the periphery. We have investigated the expression and function of E47 and E12 in IL-7-expanded pro-B/pre-B cell precursors and in unstimulated or LPS-activated splenic B cells from young and old BALB/c … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

5
77
0

Year Published

2007
2007
2019
2019

Publication Types

Select...
4
3

Relationship

1
6

Authors

Journals

citations
Cited by 79 publications
(82 citation statements)
references
References 56 publications
5
77
0
Order By: Relevance
“…In aged mice, as we have shown herein and elsewhere (3,9,11,12), pro-B/early pre-B cells have reduced overall levels of E47 protein. Although our previous studies have relied on Western blotting of lysates from pooled B cell precursors, the current study using fluorescence flow cytometry provides for determination of E47 protein expression by individual pro-B/early pre-B cells in aged mice.…”
Section: Discussionsupporting
confidence: 82%
See 2 more Smart Citations
“…In aged mice, as we have shown herein and elsewhere (3,9,11,12), pro-B/early pre-B cells have reduced overall levels of E47 protein. Although our previous studies have relied on Western blotting of lysates from pooled B cell precursors, the current study using fluorescence flow cytometry provides for determination of E47 protein expression by individual pro-B/early pre-B cells in aged mice.…”
Section: Discussionsupporting
confidence: 82%
“…Previously, we demonstrated that E2A-encoded proteins were reduced in B cell precursors derived from aged BALB/c bone marrow upon culture with recombinant mouse IL-7 (9,11,12). This reflected increased protein turnover rather than alterations in expression of E2A-encoded mRNA (12).…”
Section: B Cell Precursors Derived From Senescent Mice Exhibit Increamentioning
confidence: 83%
See 1 more Smart Citation
“…BAFF-R forward, CCC-AGA-CTC-GGA-ACT-GTC-CC; BAFF-R reverse, GTA-GAG-ATC-CCT-GGG-TTC-CAG; TACI forward, CAG-GTA-CTA-CGA-CCA-TCT-CCT-G; TACI reverse, TCG-TCG-CAA-GCC-TCT-GTC-AC; BCMA forward, CCC-ACA-GAG-AAT-CTG-CTG-TTC-TTC; BCMA reverse, AAA-GAT-CCT-GTC-GTC-ACC-AGC-CC. E2A primers amplify both E12 and E47, but E47 is the major E2A-encoded mRNA and protein in splenic B cells (Frasca et al, 2003). Subsequent experiments using E47 primers show similar results.…”
Section: Rna Extraction Reverse Transcription and Pcr (Rt-pcr)mentioning
confidence: 79%
“…We have shown (Frasca et al, 2004a) that splenic B cells from old mice have reduced levels of E47, and subsequently AID, leading to poor CSR and production of secondary isotypes in senescence. We have previously shown (Frasca et al, 2003) that in splenic mature B cells, only E47/E47 homodimeric complexes bind DNA, whereas in bone marrow B cell precursors, E47/E12 complexes participate in DNA binding. E12 is present at very low levels in activated splenic B cells from young mice and is almost undetectable in old B cells.…”
Section: Discussionmentioning
confidence: 99%